Contemporary Ink Paintings and the Future of Chinese Art - Carter, Curtis L. (Filozofski vestnik, 2016)
Why are contemporary independent experimental Chinese artists again attracted to ink painting? Artists who choose to work in the medium of ink paintings today are engaged in a search for meaningful connections between traditional philosophical and artistic means and their present-day experience. This does not mean simply painting in the manner of previous masters. Rather, it seems to me that the artists who continue to keep the ink painting tradition active today, and even incorporate it into contemporary experimental art, have chosen to explore ink painting as one way to sustain their Chinese identity, and at the same time contribute to a living tradition. As we have seen in the works of Pan Gongkai and many other contemporary Chinese artists, it is indeed possible for contemporary artists to achieve their own sense of originality and purpose while continuing to experiment with pictorial space, varied ink colorations, and brush strokes. In short, their engagement with the processes of creating new forms of ink paintings provides a meaningful link with Chinese culture as it has been imbedded in the calligraphy and ink paintings of the masters through the ages. At the same time, ink painting provides a means for creative expression and artistic production in the contemporary art world, both within China and in the global art world.